Substrate binding mechanism of glycerophosphodiesterase towards organophosphate pesticides - Nayana Bhat (2022)
Glycerophosphodiesterase (GpdQ) from Enterobacter aerogenes is a binuclear metallohydrolase, which is capable of catalyzing the hydrolysis of mono-, di-, and tri-ester substrates, including some organophosphate pesticides and degradation products of nerve agents. The GpdQ has attracted recent attention as a promising enzyme for bioremediation. This enzyme utilizes two metal ions located in the α and β sites of the enzyme active site for catalysis and is found to bind to Fe(II) ion preferentially. In this study, we aimed to investigate the binding interactions of three organophosphate pesticides (i.e., profenofos, diazinon and chlorpyrifos) to the GpdQ using computational approaches. Firstly, each pesticide molecule was separately docked into the active site of the GpdQ using molecular docking. Then, 500-ns MD simulations were carried out on the systems without (apo enzyme) and with pesticides bound. The MD results showed that the Feβ binds well with the GpdQ active site in the presence of pesticide. It is also seen that the binding of the pesticide could stabilize the enzyme structure in the active conformation, allowing the substrate to be catalysed into less harmful products. Therefore, the ability of in silico analysis presented here could be informative for enhancing enzyme stability and activity in the future.